In Vivo Corneal Biomechanical Properties in a Selected Chinese Population, Measured Using the Corneal Visualization Scheimpflug Technology - Li, Yuxin; Tian, Lei; Guo, Li-Li,; Hao, Yiran; Jie, Ying (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose. To evaluate the repeatability and reproducibility of recalculated dynamic corneal response (DCR) parameters and the biomechanical-compensated intraocular pressure (bIOP) derived from Corneal Visualization Scheimpflug Technology (Corvis ST), and to study the variations of DCR parameters and their relationship with demographic and ocular characteristics. Methods. A total of 544 healthy subjects were recruited in this study and a series of ophthalmological examinations were performed on their right eyes. Three repeated measurements were obtained at three-minute intervals for 291 of the participants to ensure reliability. A sum of 100 participants was examined twice within two-hour intervals using two different Corvis ST in the reproducibility study. The repeatability and reproducibility of 37 parameters, including 36 DCR parameters and bIOP, were assessed by coefficient of repeatability (CR), coefficient of variation (CV), intraclass correlation coefficient (ICC), and within-subject standard deviation (sw). Pearson’s correlation coefficients and stepwise multivariate linear regression models were performed to investigate whether DCR parameters were related to demographic and ocular characteristics. Results. Of all the 37 parameters, 34 showed excellent (ICC≥0.90) or good (ICC≥0.75) repeatability while 27 of the 37 parameters showed excellent (ICC≥0.90) or good (ICC≥0.75) reproducibility. In particular, a CV of less than 20% was found for all DCR parameters and bIOP. Fourteen of 36 DCR parameters was selected for correlation analysis, based on measurement reliability and clinical relevance in referring to previous literature. Age was negatively associated with Highest concavity delta arc length (HCdArcL) and peak distance (PD) but it positively correlated with Whole Eye Movement Max Length (WEMML). Intraocular pressure (IOP) and central corneal thickness (CCT) were negatively associated with deformation amplitude ratio (DARM) [1mm], A1 Velocity (A1V), and PD, while positively related to the stiffness parameter at applanation 1 (SP-A1). The bIOP was negatively associated with A1V but positively associated with A2 Velocity (A2V). Anterior chamber volume (ACV) was negatively associated with the pachy slope (PS), WEMML, and SP-A1. Conclusion. The Corvis ST showed good precision for the repeatability and reproducibility of 36 DCR parameters and bIOP parameters in healthy eyes. The IOP, CCT, bIOP, Km, and ACV significantly influenced the DCR parameters of the eyes.